Analisis Strategi Pemasaran untuk Meningkatkan Penjualan UMKM Gula Aren Pak Ileh di Desa Telagah - Annisa Khoiri; Ema Nur Syahfitri; Siti Aisyah (Jurnal Simki Economic, 2026)
The main challenges faced by Pak Ileh's palm sugar MSME partners in Telagah Village include limited raw materials, conventional marketing, and traditional factors. This study aims to analyze the marketing strategies of Pak Ileh's palm sugar MSMEs in Telagah Village and the obstacles they face in increasing sales. The study used qualitative methods through observation, interviews, and documentation. The results show that marketing still relies on product quality and offline promotions such as word of mouth and banners. Obstacles include limited raw materials, less than optimal promotion, and simple packaging without brand identity. Therefore, the use of digital media, packaging improvements, and collaboration with suppliers are needed to sustainably increase sales.